NATIONAL WAQF-BASED FOREST INDEX: TOWARDS ENVIRONMENTAL SUSTAINABILITY AND COMMUNITY EMPOWERMENT THROUGH SHARIA FINANCIAL INNOVATION - Ali, Khalifah Muhamad; Tanjung, Hendri; Sukmana, Raditya; Sari, Indah Fresma; Jannah, Miftahul; Mustaqimah, Mu'minah (Universitas Airlangga, 2025)
Currently, the existing concepts of waqf management and forest management are still separated. It creates an opportunity to develop the concept of waqf-based forest management. This study aims to develop a National Waqf-based Forest Index (NWFI) as a standardized tool to measure the performance of waqf-based forest management practices. This research is a quantitative study that began with preliminary research and was followed by interviews with seven experts using the Analytical Hierarchy Process (AHP). Based on preliminary research, the index comprises five dimensions: institution (with three aspects), process (with three aspects), system (with three aspects), outcome (with twelve aspects), and impact (with three aspects). It is found in the AHP analysis that the institution and process dimension is considered the most important aspect for waqf-based forests, with an importance score of 0.227, followed by the system and impact dimension (0.197), and the outcome dimension (0.152). Based on the consistency rate, all experts' assessments were consistent. Regarding rater agreement, the outcome dimension and several indicators related to the environment and social facilities achieved the highest level of agreement (W 0.400–0.500), whereas other dimensions and aspects, such as expert opinions, showed significant dispersion. In conclusion, this waqf-based forest index has the potential to strengthen the role of Islamic finance in supporting sustainable projects by providing the basic practical tool for the waqf-based forest nazhir and policy-makers to assess waqf-based forest management and construct future good nazhir governance. Further research and pilot projects are important to evaluate its effectiveness in measuring waqf-based forest management practically.